2005
DOI: 10.21273/hortsci.40.4.1083e
|View full text |Cite
|
Sign up to set email alerts
|

(337) Effect of Selenium Supply by Trunk Injection on Fruit Quality of `Niitaka' Asian Pear

Abstract: Many trials to supply selenium to fruit have been carried out since tests have confirmed selenium's role as a medical substance. Supplying selenium in orchards by soil and foliar application was not effective because of loss from rainfall. In order to increase selenium absorption by fruit, this study carried out tree trunk injections during the growing season. Selenium solutions in concentrations of 5, 10, 25, and 50 mg·L–1 were supplied to `Niitaka' pear (Pyruspyrifol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…These results are in the same trend with the prior results 4 , 5 , where the application of selenium increased efficiently the yield in horticultural crops. Besides, it was found that Se raised the yield in “Valencia” orange 68 , ‘Zaghlol’ date palm 90 and in ‘Starking Delicious’ apple cultivar 91 .…”
Section: Resultssupporting
confidence: 90%
“…These results are in the same trend with the prior results 4 , 5 , where the application of selenium increased efficiently the yield in horticultural crops. Besides, it was found that Se raised the yield in “Valencia” orange 68 , ‘Zaghlol’ date palm 90 and in ‘Starking Delicious’ apple cultivar 91 .…”
Section: Resultssupporting
confidence: 90%